Place–time correlation of robbery incidents in metropolitan Lagos: a Mantel index analysis. Issue 1 (2nd January 2017) - Badiora, Adewumi Israel; Ntamark, Jenny Jacky
ABSTRACT: This article investigates the correlation of space and time in the clustering of robbery incidents in metropolitan Lagos. Analysis was carried out on 781 selected robbery incidents in 2013. Using the Mantel index to correlate place and time intervals for pairs of robbery incidents, the results show that robberies are respectively concentrated in residential areas, transport nodes and public places, peaking at midnight during weekdays. The results further show that this concentration is most likely greater than what would be expected on the basis of a chance distribution. The study concludes that various factors may exist which cause clusters of robberies to occur in these places at these times.